Reconstruction of Prisoners' Rights and Its Contribution to Family Law Reform in Indonesia (Study in Lampung Province Correctional Institution - Welli, Welli (Universitas Islam Negeri Raden Intan Lampung, 2024)
This research discusses the challenges faced by prisoners in the divorce process in Indonesia, especially in relation to their civil rights. The purpose of this study is to examine the implementation of divorce law for prisoners, as well as identify shortcomings in the fulfillment of these rights. This research uses a juridical and philosophical approach with field research methods, including interviews with relevant parties in correctional institutions and analysis of divorce data in religious courts. The findings show that many inmates are unable to attend divorce hearings, which reduces their opportunity to defend their rights and that the provision of children's education rights in LPKA has not been effective. Based on these findings, it is suggested that there should be a policy reconstruction that allows prisoners to be present in divorce proceedings, either in person or through communication technology, as well as standardizing the provision of educational rights for children of prisoners in LPKA. This research provides recommendations for family law reform in Indonesia that are more inclusive and equitable.Keywords: Reconstruction of Prisoners' Rights, LAPAS and LPKA Lampung, Family Law Reform